Joint video/depth rate allocation for 3D video coding based on view synthesis distortion model - Liu, Yanwei; Huang, Qingming; Ma, Siwei; Zhao, Debin; Gao, Wen (Signal processing. Image communication, 2009)
Joint video/depth rate allocation is an important optimization problem in 3D video coding. To address this problem, this paper proposes a distortion model to evaluate the synthesized view without access to the captured original view. The proposed distortion model is an additive model that accounts for the video-coding-induced distortion and the depth-quantization-induced distortion, as well as the inherent geometry distortion. Depth-quantization-induced distortion not only considers the warping error distortion, which is described by a piecewise linear model with the video power spectral property, but also takes into account the warping error correlation distortion between two sources reference views. Geometry distortion is approximated from that of the adjacent view synthesis. Based on the proposed distortion model, a joint rate allocation method is proposed to seek the optimal trade-off between video bit-rate and depth bit-rate for maximizing the view synthesis quality. Experimental results show that the proposed distortion model is capable of approximately estimating the actual distortion for the synthesized view, and that the proposed rate allocation method can almost achieve the identical rate allocation performance as the full-search method at less computational cost. Moreover, the proposed rate allocation method consumes less computational cost than the hierarchical-search method at high bit-rates while providing almost the equivalent rate allocation performance.